2001
DOI: 10.1093/nar/29.20.e97
|View full text |Cite
|
Sign up to set email alerts
|

Random multi-recombinant PCR for the construction of combinatorial protein libraries

Abstract: Development of a new methodology to create protein libraries, which enable the exploration of global protein space, is an exciting challenge. In this study we have developed random multi-recombinant PCR (RM-PCR), which permits the shuffling of several DNA fragments without homologous sequences. In order to evaluate this methodology, we applied it to create two different combinatorial DNA libraries. For the construction of a 'random shuffling library', RM-PCR was used to shuffle six DNA fragments each encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…There have already appeared several technologies in this context: 'micro gene' methods which random-assembles DNA fragments [7], systemic circular permutation of proteins [8], random multirecombinant polymerase chain reaction (RM-PCR) [9] and incremental truncation for creating hybrid enzymes [10]. Recently, we developed the Y-ligation-based block shu¥ing (YLBS) method for the purpose of general recombination [11].…”
Section: Introductionmentioning
confidence: 99%
“…There have already appeared several technologies in this context: 'micro gene' methods which random-assembles DNA fragments [7], systemic circular permutation of proteins [8], random multirecombinant polymerase chain reaction (RM-PCR) [9] and incremental truncation for creating hybrid enzymes [10]. Recently, we developed the Y-ligation-based block shu¥ing (YLBS) method for the purpose of general recombination [11].…”
Section: Introductionmentioning
confidence: 99%
“…Equal amounts of the 36 dimer templates (each containing two building blocks) and 12 dimer templates containing 5' or 3' consensus sequences were mixed in the reaction mixture to obtain a library in which every position of the block sequences generated has an equal probability of encoding each of the six building blocks. Our previous study showed that many block sequences in which six building blocks were arranged into different orders were successfully constructed using this procedure [48]. Further, recently we confirmed that RM-PCR successfully combined 13 building blocks with different lengths, taken from different proteins.…”
Section: Random Multi-recombinant Pcr (Rm-p C R ) F O R T H E C O N Smentioning
confidence: 64%
“…To realize this concept it was necessary to develop a novel strategy capable of combining different DNA fragments without homologous sequences. We developed random multi-recombinant PCR (RM-PCR) [48,49] based upon overlap extension PCR [50]. Fig.…”
Section: Random Multi-recombinant Pcr (Rm-p C R ) F O R T H E C O N Smentioning
confidence: 99%
“…However the efficient random recombination of heterologuous sequences largely remains a challenge. It has been achieved in vitro through various techniques of randomized assembly ligation and overlap extension PCR (1)(2)(3)(4)(5). However these techniques are limited in the size and number of elements they can combine.…”
Section: Introductionmentioning
confidence: 99%